HOW DOES IT FEEL TO BE SEEN BY A MACHINE LIVELY DEVICES IN DIGITAL HORROR - Gunderson, Marianne (AoIR Selected Papers of Internet Research, 2020)
What does it feel like to be watched by a machine? How do we make sense of our present state of concurrent awareness of and obliviousness of living our everyday lives under ubiquitous surveillance? This presentation will explore these questions through an analysis of a selection of creepypasta stories that draw their horror from the experience of being watched by - or through - a machine. Conceptualized as “digital urban legends” and “contemporary folklore” creepypastas are short internet-based horror stories often posted anonymously and copied and pasted from forum to forum and collected in online archives.The stories analysed in this paper bring their horror to the technological devices that permeate our everyday lives, such as web cameras, GPS navigation, home security systems, and baby monitors. In these stories, the topic of surveillance and the experience of being watched is a pervasive theme, and quotidian technological devices take on a threatening presence. Sometimes the threat is connected to the idea of surveillance by nefarious corporations or hostile individuals, while in other stories the horror emerges from the realization that the watcher is not human at all. Combining horror tropes with the idea of digital surveillance, these stories function as affective articulations that reveal the anxieties that haunt our relationship with the devices with which we surround ourselves. Through its analysis, this paper argues that the fears articulated in these stories revolve around how machine vision technologies mediate our relationship with reality and redistribute agency within human/machine assemblages.